#Blessed: An exploratory analysis of allusion as a descriptive literary device for transactional sex relationships in fiction (Namibian Journal of Linguistics, Literature and Communication Studies, 2024)
This article explores the creative use of allusion as a literary device in the description of transactional sex relationships in the following selected literary texts; The Blessed Girl by Angela Makholwa (2018), Bare: #The Blesser Game by Jackie Phamotse (2017) and The Y in yOUR Man is Silent: Book 1 by Yvonne Maphosa (2019). The discovery of the dearth of literature on the portrayal of transactional sex relationships in fiction catalysed this article. Thus this article sought to explore the diverse creative ways in which allusion is employed to describe the relatively new phenomenon of transactional sex relationships. In this article, a qualitative desktop literary analysis was the methodology of choice. The article employed the critical lens of Lipstick Feminism which advances the use of make-up and sexual appeal as an empowerment tool for women without regarding how it sustains the commodification of transactional sex relationships. The significant finding of the study was that the creative use of allusion was crucial as they exemplify the blessee's lifestyle. The brand names are significant in shaping the blessee's archetype and image. In conclusion, allusion was effectively used in the selected works of fiction to describe the new phenomenon of transactional sex relationships.
Keywords: allusion; transactional sex relationships; fiction; blessee; side-chick; brands